The effects of red blood cell infusion on 10-km race time - Brien, A. J.; Simon, T. L. (Journal of the American Medical Association, 1987)
The purpose of this study was to investigate the effect of infusion of 400 mL of red blood cells (RBCs) on 10-km track race time, submaximal heart rate, hematocrit, 2,3-diphosphoglycerate, and partial pressure of oxygen at 50% hemoglobin saturation. Six highly trained, male, distance runners twice donated a unit of RBCs, which was frozen for subsequent reinfusion. Eleven weeks after the second donation, they undertook a series of three competitive 10-km races on a standard 400-m track: before infusion, after 100 mL of saline solution, and after 400 mL of autologous, previously frozen deglycerolized RBCs. All subjects took all trials in this double-blind, placebo, crossover, experimental design. Running time was recorded at each 400-m split, and blood was collected prior to each trial. The data were analyzed by analysis of variance. Results following the RBC infusion showed a significantly higher hematocrit concentration, a significantly faster 10-km run, a nonsignificant decrease in submaximal heart rate (10 beats faster 10-km run, a nonsignificant decrease in submaximal heart rate (10 beats per minute), and no significant changes in either 2,3-diphosphoglycerate or partial pressure of oxygen at 50% hemoglobin saturation. Erythrocythemia induced by the infusion of 400 mL of autologous packed RBCs effectively increased performance capacity in a 10-km track race, probably due to an increase in oxygen delivery to the working muscles.